Effect of chamomile aromatherapy with and without oxygen on pain of women in post cesarean section with spinal anesthesia: A randomized clinical trial. Issue 4 (April 2023) - Zamani Habibabad, Hajar; Afrasiabifar, Ardashir; Mansourian, Afshin; Mansourian, Mahboubeh; Hosseini, Nazafarin
Abstract: Background: Pain is the most common side effect in cesarean section with spinal anesthesia. It seems that oxygen therapy and chamomile aromatherapy may diminish pain. The present study was conducted to examine and compare the effect of chamomile aromatherapy with and without oxygen on the severity of pain of women following cesarean section surgery with spinal anesthesia. Methods: The present randomized clinical trial study was carried out on 136 women undergoing cesarean section surgery with spinal anesthesia at Imam Sajad Hospital, Yasuj, Iran in 2020. The eligible women were assigned into four 34-member groups including oxygen therapy plus aromatherapy, oxygen therapy, aromatherapy, and control via block randomization. Each of these interventions were performed 6, 6.30 and 7 h post operation. In the first intervention group, one drop of chamomile essential oil with distilled water was poured into a small nebulizer using a simple mask connected to 6 L of oxygen. The second intervention group received oxygen without chamomile aromatherapy at similar times, and the third intervention group received chamomile aromatherapy without oxygen. The control group received only routine interventions. The instrument used in the research was visual analog scale which was completed by the researcher 6, 12, 18 h after cesarean section. The data were analyzed by the SPSS software version 20. Results: There was a significant difference in the intensity of pain of patients between the various groups of study following the interventions (P < 0.001). Pain intensity reduced significantly in the group receiving combined intervention of chamomile aromatherapy plus oxygen compared to the other three groups. Moreover, the pain intensity diminished more in the groups undergoing each of these interventions alone as compared to the control group (P < 0.05). Conclusions: The combined intervention of chamomile aromatherapy with oxygen was more effective than each of the chamomile aromatherapy and oxygen interventions alone in reducing the pain of cesarean section patients though each intervention alone was still effective in lowering pain post-operation.